PENGGUNAAN MULTIMEDIA INTERAKTIF DALAM PENINGKATAN MOTIVASI BELAJAR AQIDAH AKHLAK - Yuslinda Yuslinda (IQRO: Journal of Islamic Education, 2018)
This study aims to determine the application of interactive multimedia in increasing motivation to  learn aqidah morals in MTs Pondok Pesantren Darul 'Ulum  Ath-Thahiriyah Paladang. The purpose of  this  thesis  was to  obtain empirical data on character motivation to  learn  aqidah  before  taught  using interactive  multimedia and  to  obtain information on whether the application of interactive multimedia can enhance learning motivation of students in MTs Pondok Pesantren Darul  'Ulum  Ath-Thahiriyah.